Decoding the Sustainability-Finance Nexus: Green Bonds and Their Interactions with Global Financial Indicators (International Journal of Environmental Sciences, 2025)
This study explores the dynamic interactions between green bonds and major global financial indicators, green bonds, global commodity and equity indices, Bitcoin, crude oil, and US dollar index, employing Granger causality tests and a Vector Autoregression (VAR) framework. The empirical results underscore the responsiveness of green bonds, represented by the S&P Green Bond Index (SPGB), to global equity market movements, particularly the MSCI Global Equity Index (MSCIE). A strong unidirectional causality from MSCIE to SPGB suggests that green bond performance is shaped significantly by trends in global equity markets, reflecting broader macroeconomic sentiment and capital availability for sustainable investments. Additionally, the bidirectional causality between MSCIE and the US Dollar Index (USDX) illustrates the tight interlinkage between currency dynamics and global equity flows. In contrast, the analysis finds no significant causal relationship between green bonds and more speculative or volatile assets such as crude oil and Bitcoin, likely due to differences in investor profiles, investment horizons, and market structures. The VAR results further validate that green bonds are primarily influenced by their own lags and by equity and currency markets, with limited influence on other assets. These findings suggest that green bonds currently play a reactive rather than leading role in the global financial ecosystem, shaped by their emerging status, relatively lower liquidity, and alignment with ESG-focused investment mandates.